2022
DOI: 10.1002/jhet.4549
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of novel indole‐oxadiazole molecular hybrids by a regioselective C‐3 sulfenylation of indole with 1,3,4‐oxadiazole‐2‐thiols using iodine‐dimethyl sulfoxide and their anticancer properties

Abstract: Novel indole-oxadiazole molecular hybrids have been synthesized by a regioselective C-3 sulfenylation of indoles with 1,3,4-oxadiazole-2-thiols for the first time using iodine as a catalyst and DMSO as a co-oxidant. No other regioisomeric products were formed when the 3-position of the indole is substituted.The method is mild and highly efficient with good substrate tolerance in both components. The indole-oxadiazole hybrid compounds are tested for their antiproliferative activities against human breast carcin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 58 publications
0
5
0
Order By: Relevance
“…Many kinds of research have been focused to discover hybrid chemical agents with antimitotic activities [ 86 ], including indole-heterocycles hybrids derivatives with promising anticancer activities [ 87 , 88 ]. Pyrazole-oxindole derivatives were also developed and evaluated on tubulin polymerization, and different kinds of cancer cell lines such as HeLa, A549, and MCF7, St.25, St.26, and St.27 ( Figure 7 ), exhibited anti-tubulin activities with IC 50 values in the range 5.90–9.20 μM [ 89 ].…”
Section: Indole Analoguesmentioning
confidence: 99%
“…Many kinds of research have been focused to discover hybrid chemical agents with antimitotic activities [ 86 ], including indole-heterocycles hybrids derivatives with promising anticancer activities [ 87 , 88 ]. Pyrazole-oxindole derivatives were also developed and evaluated on tubulin polymerization, and different kinds of cancer cell lines such as HeLa, A549, and MCF7, St.25, St.26, and St.27 ( Figure 7 ), exhibited anti-tubulin activities with IC 50 values in the range 5.90–9.20 μM [ 89 ].…”
Section: Indole Analoguesmentioning
confidence: 99%
“…[136][137][138][139][140][141][142][143][144][145][146][147][148][149][150] Dutta and group studied the importantnce of the presence of the thioether linkage in these hybrids, which can be prepared using an iodine-catalyzed synthetic route (Scheme 12). [151] They have accomplished the transformation using indole and oxadiazolethiols as the precursors. The use of 10 mol% of iodine as catalyst and 2 equivalents of DMSO as an oxidant produced the desired product.…”
Section: Csp 2 à S Bond Formationmentioning
confidence: 99%
“…Further studies revealed that the incorporation of isobenzofuran or thioether between indole and 1,3,4-oxadiazole moieties could not improve the activity. [77,78]…”
Section: Indole/isatin-azole Hybridsmentioning
confidence: 99%